Integrating Stakeholder Input to Develop a Robotic Gait Training Intervention for People With Spinal Cord Injury: A Brief Report - Megan Douglas; Faith Meza; Seema Sikka; Simon Driver; Dale Anderle; Ashley Barnes; Chad Swank (Journal of Participatory Research Methods)
Individuals with disability, like survivors of spinal cord injury (SCI), are necessary partners in the development of evidence-based health promotion programs. As a Community-Based Participatory Research approach is often difficult to feasibly implement for certain time-limited projects, we utilized a community advisory board (CAB), including individuals with SCI lived experience, to develop a robotic exoskeleton gait training program during inpatient rehabilitation using a randomized clinical trial (RCT) design. We describe how we identified and included individuals with lived experience into our CAB from the proposal stage through study execution. Phases of engagement included: 1) collaboratively adapting the program, 2) refining the program and study procedures and measures, and 3) collecting data and reviewing outcomes. We also conducted a lived experience consultant survey following conclusion of the project. Several changes were made to the RCT based on CAB input, including changing inclusion and exclusion criteria, utilizing the clinical team, adjusting the protocol to reflect patient clinical needs, and changes to data collection measures. Overall, engagement and feedback suggest our approach was successful in engaging community members throughout all phases of our multi-year RCT. Retention of CAB members was excellent with an average attendance of 70% across all quarterly meetings. Survey feedback suggests that individuals with lived experience considered their input valuable and meaningful. Suggestions for changes included increasing compensation, balancing virtual and in-person meetings, and utilizing people with lived experience for recruitment efforts.